Pengaruh Time Budget Pressure, Kompetensi, dan Pengalaman Auditor terhadap Kualitas Audit dengan Etika Profesi Auditor sebagai Pemoderasi (Studi Kasus pada Badan Pemeriksa Keuangan Republik Indonesia Perwakilan Provinsi Kalimantan Barat) - JUN, LIE (Jurnal KIAFE, 2022)
This research's objective was to determine the effects of time budget pressure, auditor competence, and audit experience on audit quality, with the profession's ethics serving as a moderating variable. This research population was the entire auditor who worked in the office of Badan Pemeriksa Keuangan Perwakilan Provinsi Kalimantan Barat. Techniques for data analysis was utilizing the Structural Equation Modeling (SEM) method with the Partial Least Square (PLS) method and the WarpPLS 7.0 software. The results showed that time budget pressure had a negative impact on audit quality, competence had a positive impact on audit quality, and the experience of the auditor positively affected audit quality. The impact of time budget pressure and The auditing profession's ethics reduced audit quality skill, and enhanced the effect of auditor experience on audit quality.Keywords : Time Budget Pressure, Auditor Competence, Audit Experience, Auditing Profession's Ethics, Audit Quality